Socio-economic benefits of community forestry in the North Caribbean Coast Autonomous Region, Nicaragua. Report submitted to the ADA Community Forestry Project in Mesoamerica. - Arguello Perez, J.; Stoian, D. (2016)
This report presents the results of a socio-economic study conducted in three communities in Nicaragua's North Caribbean Coast Autonomous Region (RACCN), as part of the fourth component (Value Chains) of the project "Forestry to enhance livelihoods and sustain forests in Mesoamerica: How institutional arrangements and value chains affect benefits and resources", executed by Bioversity International, BOKU, CATIE and Masangni. This research has been supported by the Austrian Development Agency (ADA) with funds of Austrian Development Cooperation (ADC), CGIAR Fund Donors, and the CGIAR Research Program on Forest, Trees and Agroforestry. The general objective of this study was to determine the socio-economic benefits derived from community forestry at household and enterprise level in three RACCN communities.